DAMPAK PENERAPAN PUNGUTAN EKSPOR CRUDE PALM OIL TERHADAP KINERJA AGRIBISNIS KELAPA SAWIT DAN PENDAPATAN PETANI INDONESIA - ., Maswadi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2012)
Crude Palm Oil (CPO) is a strategic commodity in the economy ofIndonesia. CPO industry also plays an important role in the internationalmarket. The rate of growth of production of CPO is the highest among thecategories of oil consumed. Even a CPO has predicted will pass trade oilfor soybeans at most in the world market be trading.The current Government had new instruments in international tradeactivities, i.e. the export levy of dilegalisasi on September 10, 2005 withthe publication of legislation No. 33 of 2005. Broadly speakingstakeholders agribusiness palm national associate substance of the purposeand size of the export levy rate as well as benchmark price export withbenefit dimension, justice and legal certainty. After looking closely atlegislation of the export levy in the perspective of the development of oilpalm industry, there are 2 national article that needs to be understood indepth. The second chapter is chapter 2, about the purpose and article 3paragraph 5 and 6, of the size of export the levy rate and export benchmarkprices. Both articles still contain questions like: